MERDEKA BELAJAR DALAM PERSPEKTIF HUMANISME CARL R. ROGER - Fransiskus Sili (STKIP Persada Khatulistiwa Sintang, 2021)
Merdeka Belajar is an educational reform movement that is based on empowering teacher creativity and innovation in creating meaningful learning in the classroom. The reality shows that in terms of concept and implementation, independent learning has not been fully understood and applied successfully. The policy of free learning with its current stages needs to be supported by strengthening the concept of humanity and its development. This literature study explores Carl Roger's ideas as an alternative to broaden the idea of humanity and its implications in education. Data sources use books, journal articles, and website articles. Carl Roger's ideas from various sources were studied, analyzed, and then drawn conclusions inductively to get a conceptual conclusion that could be applied at the educational level. The research results show that Carl Rogers' humanism is in line with the ideas and policies of independent learning that are directed at building and developing a complete, integral, and true self-image of students. To create a complete identity of a studentas an independent human being, education must prioritize the aspects of love, respect for the child's personality so that freedom of thought, initiative, and creativity is built.